2019
DOI: 10.1002/sce.21499
|View full text |Cite
|
Sign up to set email alerts
|

Early informal STEM experiences and STEM identity: The importance of talking science

Abstract: In this paper, we examine the relationship between participants’ childhood science, technology, engineering, and mathematics (STEM) related experiences, their STEM identity (i.e., seeing oneself as a STEM person), and their college career intentions. Whereas some evidence supports the importance of childhood (i.e., K‐4) informal STEM education experiences, like participating in science camps, existing research does not adequately address their relationship to STEM career intention later in life. Grounding our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
158
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(214 citation statements)
references
References 54 publications
2
158
0
6
Order By: Relevance
“…Specific to STEM, parental involvement and interaction are thought to have important influences on students' science engagement and identification with science. Talking with friends and family about science and exposure to science media in childhood have been shown to predict STEM identity in college (Dou et al, 2019). The influence of family support in the success of women and students of color in STEM should be further investigated, to assess strategies that could strengthen familial advocacy for youth aspiring to enter STEM fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific to STEM, parental involvement and interaction are thought to have important influences on students' science engagement and identification with science. Talking with friends and family about science and exposure to science media in childhood have been shown to predict STEM identity in college (Dou et al, 2019). The influence of family support in the success of women and students of color in STEM should be further investigated, to assess strategies that could strengthen familial advocacy for youth aspiring to enter STEM fields.…”
Section: Discussionmentioning
confidence: 99%
“…Media images often depict men and women in traditional gender roles, which can negatively impact the STEM career choices women make (Olsson and Martiny 2018;Bian, Leslie, & Cimpian, 2017). Dou, Hazari, Dabney, Sonnert, and Sadler (2019) found that talking with friends and family about science and consuming science media in childhood were predictive of STEM identity in college. The types of media that students are being exposed to are rapidly changing, and the current generation of students spends a great deal of time interacting with media platforms and gaining exposure to social media influencers (Pew Research Center, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Science identity means to think of oneself as related to science (Brickhouse, Lowery, & Schultz, ) or as the kind of person who does science (Gee, ). It has been shown to be a precursor of STEM engagement and persistence (Basu, ; Brotman & Moore, ; Carlone & Johnson, ; Dou et al, ; Hazari, Sadler & Sonnert, ; Hazari, Sonnert, Sadler, & Shanahan, ; Graham, Frederick, Byars‐Winston, Hunter, & Handelsman, ; Lee, ; Morgan, Isaac, & Sansone, ; Porfeli, Lee, & Vondracek, ; Regan, DeWitt, Henriksen, Dillon & Ryder, ; Tytler, ). To encourage the formation of science identity among girls, many scholars and practitioners have suggested to assign same‐gender science teachers to students so that the teachers can serve as gender role models (Day & Allen, ; Fox, ; Nixon & Robinson, ; Ost, ; Pascarella & Terenzini, ; Pascarella & Terenzini, ; Robst, Keil, & Russo, ).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of factors have been identified as contributing to a male‐dominant culture in the STEM professions, which in turn poses stereotype threats to women (Hazari et al, ). Background factors include gender differences in parental support (Alexander, Johnson, & Kelley, ; Crowley, Callanan, Tenenbaum, & Allen, ), teacher support (Patall et al, ), and prior enjoyable science experiences (Dou, Hazari, Dabney, Sonnert, & Sadler, ; Jones et al, ; Maltese & Tai, ; Moller, Stearns, Southworth, & Potochnick, ; Riegle‐Crumb, Moore, & Ramos‐Wada, ). Social factors include a discriminatory (Griffith, ; Hall & Sandler, ; Solnick, ), segregated (Archer, Dewitt, & Osborne, ; Charles & Bradley, ; Morton & Parsons, ; Sikora & Pokropek, ), and harassing study or work space (Clancy, Nelson, Rutherford, & Hinde, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hazari et al () found that students' physics classroom experience predicted their physics identity, which, in turn, predicted their intention to choose a career in physics. Similarly, Goff, Mulvey, Irvin, and Hartstone‐Rose () found that young people who reported participation in informal programs prior to college also reported higher academic aspirations and greater interest and engagement with STEM (see also Dou, Hazari, Dabney, Sonnert, & Sadler, ). Supporting the development of science identities has the potential to afford equal access to science (Pattison et al, ; Williams et al, ).…”
Section: Background and Conceptual Frameworkmentioning
confidence: 95%